Questions of Civil Society : Category-Position-Functionality. - Jarosz, Adam (CGS studies ;, 2013)
This book is devoted to questions and research problems generated by the issue of civil society. It contains contributions from mostly young scientists, who develop various approaches to the position and functionality of civil society, examining different examples from both the past and the present, based on theoretical approaches to this concept. As a result, the volume adopts an interdisciplinary perspective, which allows the identification of various levels of the concept of the civil soci ...